2017
DOI: 10.1021/acs.est.7b00846
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and Lipidomics of the Environmental Strain Rhodococcus ruber Point out Consumption Pathways and Potential Metabolic Bottlenecks for Polyethylene Degradation

Abstract: Polyethylene (PE), one of the most prominent synthetic polymers used worldwide, is very poorly biodegradable in the natural environment. Consequently, PE represents by itself more than half of all plastic wastes. PE biodegradation is achieved through the combination of abiotic and biotic processes. Several microorganisms have been shown to grow on the surface of PE materials, among which are the species of the Rhodococcus genus, suggesting a potent ability of these microorganisms to use, at least partly, PE as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 36 publications
8
58
0
Order By: Relevance
“…Interestingly, a recent study focused on soluble oxidized oligomers showed that 95% of these compounds were assimilated by a strain of Rhodococcus rhodochrous after 240 days of incubation (Eyheraguibel et al, 2017). The polymer is broken down into small oligomers of 600 Da incorporated in the cells by carriers belonging to the Major Facilitor Superfamily (MFS) or harboring ATP binding cassettes (ABC) (Gravouil et al, 2017). β-oxidation transforms oxidized carboxylic molecules (having an even number of carbon atoms) into acetyl coA or propionyl coA (if odd number of carbons).…”
Section: How Much Can Microorganisms Participate In Plastic Degradatimentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a recent study focused on soluble oxidized oligomers showed that 95% of these compounds were assimilated by a strain of Rhodococcus rhodochrous after 240 days of incubation (Eyheraguibel et al, 2017). The polymer is broken down into small oligomers of 600 Da incorporated in the cells by carriers belonging to the Major Facilitor Superfamily (MFS) or harboring ATP binding cassettes (ABC) (Gravouil et al, 2017). β-oxidation transforms oxidized carboxylic molecules (having an even number of carbon atoms) into acetyl coA or propionyl coA (if odd number of carbons).…”
Section: How Much Can Microorganisms Participate In Plastic Degradatimentioning
confidence: 99%
“…Carboxylation of propionyl coA into succinyl coA is performed by propionyl-coA carboxylase. Gravouil et al (2017), propose identification of an overexpressed enzyme, when the bacteria find PE in the medium (Gravouil et al, 2017). Acetyl coA and succinyl coA enter the tricarboxylic acid (TCA) cycle (Figure 4).…”
Section: How Much Can Microorganisms Participate In Plastic Degradatimentioning
confidence: 99%
See 1 more Smart Citation
“…Several microorganisms have been shown to grow on the surface of PE materials, among which are the species of the genus Rhodococcus, suggesting a potent ability of these microorganisms to use, at least partly, PE as a carbon source (Table 2). However, most Rhodococcus species, if not all, fail to induce a clear-cut degradation of PE samples [82]. A number of recent papers have identified, isolated, and chararcterized PE degradation by marine bacteria [83,84], including Alcanivorax borkumensis [85].…”
Section: Type Of Microorganisms Usedmentioning
confidence: 99%
“…Oleaginous strains of Rhodococcus sp. tend to store intracellular carbon-rich lipid in nitrogen limiting conditions, for instance while degrading non-nitrogen containing hydrocarbons, such as phenol, polyethylene and anthracene (Yoneda et al, 2016; Goswami et al, 2017; Gravouil et al, 2017). As 4-NP degradation provides both carbon and nitrogen for growth, the absence of nitrogen limitation is likely responsible for the observed lipid deterioration in BUPNP1 growing on 4-NP.…”
Section: Discussionmentioning
confidence: 99%